PRODUCTIVITY OF FILM AND NAKED OATS, DEPENDING OF A SEEDING RATE - Форемна, І. В.; Лихочвор, В. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article presents results of field experiments concerning formation of yield capacity of film and naked grain of oats, depending on a seeding rate, under conditions of the Western forest-steppe of Ukraine. Results of the experiments confirm that the highest yield capacity is obtained under the seeding rate of 6,0 million/ha. Under such rate, yield capacity of film cultivar Desnianskyi constituted 4,61 ton/ha and naked cultivar Avhol – 4,09 ton/ha. Some lower yield capacity of oats grain was obtained under the seeding of 5,0 million/ha. The lowest yield of the studied cultivars was observed in the variants, where the seeding rate constituted 3,0 million/ha. Indicators of the oats grain quality changed under the impact of seeding rates. The maximum content of protein and fat in oats was obtained in the variant, where the seeding rate constituted 3,0 million/ha, and minimum one – under the plant density of 6,0 million/ha